Comparative analysis of newly identified rodent arteriviruses and porcine reproductive and respiratory syndrome virus to characterize their evolutionary relationships - Zhao, Zhuang-Yan; Yu, De; Ji, Chun-Miao; Zheng, Qiankun; Huang, Yao-Wei; Wang, Bin (Frontiers in Veterinary Science, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) has caused huge economic losses for the global pig industry, but its origins and evolution remain a mystery. In 2018, the genome sequences of seven arteriviruses isolated from rodents were determined, and here we publish new analysis showing that they may be ancestors of PRRSV. The sequence similarity of these viruses to PRRSV was 60%, with shared genome organization and other characteristics, such as slippery sequences and C-rich motifs in nsp2, and a transactivated protein sequence in nsp1β. Codon usage basis analysis showed that PRRSV was closer to these rodent arteriviruses than lactate dehydrogenase-elevating virus (LDV) and they were both under pressure of natural selection. Evolutionary analysis revealed that four of the rodent arteriviruses shared the same genus with PRRSV, and were more closely related to PRRSV-2 than PRRSV-1. In addition to this, they all appeared earlier than PRRSV according to evolutionary modeling, and we speculate that they represent an intermediate step in the origin of PRRSV by arterivirus transmission from rodents to swine. Our in-depth analysis furthers our understanding of arteriviruses, and will serve as the basis for subsequent exploration of the evolution of PRRSV and other arteriviruses.